1993
DOI: 10.1055/s-2006-959853
|View full text |Cite
|
Sign up to set email alerts
|

Ancistrocladus robertsoniorum“Produces” Pure Crystalline Droserone when Wounded

Abstract: P/ante Med. 59. Supplement Issue 1993 figurations at the axes. The only example for atropisomeric pairs in this plants is the fully dehydrogenated alkaloid dioncophyllacine A, which occurs as a mixture of its atropoenantiomers 4 and ent-4 (8).The first occurrence of atropo-diastereomeric representatives, though only in minor amounts, is also of pharmacological interest, since it now allows us to investigate the influence of the configuration at the axis on the biological activity. AcknowledgementsThis work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…2 ). Droserone was identified in several plant families, for example, Plumbaginaceae ( Dinda et al , 1995 ), Nepenthaceae ( Likhitwitayawuid et al , 1998 ), Droseraceae ( Kreher et al , 1990 ; Budzianowski, 2000 ), and Dioncophyllaceae ( Bringmann et al , 2000 ) and was shown to exert antimalarial ( Likhitwitayawuid et al , 1998 ) and pesticidal activities ( Bringmann et al , 1993 ; Bringmann and Feineis, 2001 ). Me-droserone is rare in nature and was only identified in Diospyros melanoxylon Roxb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ). Droserone was identified in several plant families, for example, Plumbaginaceae ( Dinda et al , 1995 ), Nepenthaceae ( Likhitwitayawuid et al , 1998 ), Droseraceae ( Kreher et al , 1990 ; Budzianowski, 2000 ), and Dioncophyllaceae ( Bringmann et al , 2000 ) and was shown to exert antimalarial ( Likhitwitayawuid et al , 1998 ) and pesticidal activities ( Bringmann et al , 1993 ; Bringmann and Feineis, 2001 ). Me-droserone is rare in nature and was only identified in Diospyros melanoxylon Roxb.…”
Section: Discussionmentioning
confidence: 99%
“…Droserone, the oxygenated derivative of plumbagin, is synthesized in a variety of Nepenthales species ( Bringmann et al , 2000 ; Budzianowski, 2000 ). It lacks immunostimulating activity ( Kreher et al , 1988 ), but exhibits anti-malarial and possibly pesticidal activity ( Bringmann et al , 1993 ; Bringmann and Feineis, 2001 ). Other small modifications in the naphthoquinone core structure lead to marked differences in activity and, consequently, also in toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Droserone was shown to have no immunomodulating activity in contrast to plumbagin and hydroplumbagin glucoside (5). However, it has some antimalarial activity (13) and possibly protective and/or pesticidal properties (14). The latter, similar role was suspected for hydroxydroserone (2).…”
mentioning
confidence: 90%